Efeito da infecção aguda por Strongyloides venezuelensis na evolução da colite experimentalmente induzida pela ingestão de Sulfato de Sódio Dextrano em camundongos BALB/c - Vanessa Fernandes Rodrigues (2015)
Inflammatory bowel diseases (IBD), such as Crohn's disease and ulcerative colitis, showed increasing prevalence among North American and European population that was associated with better medical and hygiene conditions. Currently, IBD affect millions of people worldwide. The etiology of these inflammatory diseases is not fully understood; however, studies indicate that several factors can act in the induction of an inappropriate immune response to intestinal antigens with subsequent establishment of the intestinal inflammation. Epidemiological studies and experimental evidences indicate that the immune response induced by helminth parasites can reduce the severity of inflammatory bowel disease. However, the mechanisms that operate in the modulation of inflammatory bowel disease are not fully understood, and mechanistic differences among the studies would be related to different helminth species and stage of infection. In the present study we evaluated the effect of Strongyloides venezuelensis acute infection on the clinical course of ulcerative colitis induced by dextran sulfate sodium (DSS). S. venezuelensis infected or not infected BALB/c mice were treated orally with 4% DSS aqueous solution during 7 days. During the treatment with DSS, animals of the different experimental groups were comparatively evaluated for the clinical signs related to the severity of colitis and intestinal inflammation. The data showed that the acute infection with S. venezuelensis was able to significantly reduce the clinical score of colitis induced by DSS treatment. Clinical improvement of animals infected and treated with DSS was followed by reversal of the colon shortening and reduction of macroscopic lesions in large intestine. It was also shown that mice previously infected by S. venezuelensis and treated with DSS initially showed an initial reduction of IL-4, INF- and IL-17 and later increasing in IL-4 and IL-10 concentration in the colon homogenate as compared to animals treated only. Infection with S. venezuelensis also resulted in significant reduction eosinophil and neutrophil activation, but goblet cells and mucus production in colon mucosa was preserved in this experimental group. Our data demonstrate that S. venezuelensisa cute infection modulates DSS-induced ulcerative colitis in mice. This effect is possibly mediated by initial suppression of pro-inflammatory cytokines local production and granulocyte migration and subsequent increase of anti-inflammatory cytokines in colon.